Kinetic Study of the Azo – Hydrazone Photoinduced Mechanism in Complexes with a -Re(Co)3l0/+ Core by Flash Photolysis - Mascayano-Collado, C; Godoy-Gonzalez, F; Godoy-Gonzalez, F; Gomez-San Martin, A; Gomez-San Martin, A; Flores-Vergara, E; Flores-Vergara, E (Elsevier B.V., 2023)
The photoprocesses of three rhenium(I) tricarbonyl complexes, fac-Re(NN)(CO)3L0/+, bearing an azo/hydrazone ligand, NN, and L = Cl, Br or CH3CN as axial ligand, were studied by time-resolved spectroscopic techniques. Flash irradiation of deaerated solutions of the complexes in acetonitrile photogenerated intermediates with intense optical absorptions in the UV–vis spectral region of the hydrazone ligand. The decay of the intermediates photogenerated with the Cl, Br and CH3CN ligands in the axial position proceeds by three different mechanisms. For the fac-Re(NN)(CO)3Cl, a three-step mechanism involving isomerization, tautomerization and rotation accounts for the spectroscopic transformations. In contrast to the flash photolysis result, the continuous photolysis of the complex in acetonitrile does not show spectroscopic changes associated with the generation of a stable product, i.e., the complex exhibits a photoreversible behavior. The first step observed in the flash irradiation of fac-Re(NN)(CO)3Cl, is missing in the decay of the photogenerated intermediates with fac-Re(NN)(CO)3Br and fac-[Re(NN)(CO)3CH3CN]+. A possible reason for this absence is that the process is too fast for the time-response of the flash photolysis set-up. Time-resolved spectra and associated reaction rate data for the Re(I) complexes are communicated and discussed. DFT calculations support a plausible E → Z mechanism with thermal back-isomerization mediated by tautomerization. © 2023 Elsevier B.V.